2013
DOI: 10.1063/1.4812049
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of the normal coefficient of restitution for wet impacts

Abstract: Abstract.A thorough understanding of the energy dissipation in the dynamics of wet granular matter is essential for a continuum description of natural phenomena such as debris flow, and the development of various industrial applications such as the granulation process. The coefficient of restitution (COR), defined as the ratio between the relative rebound and impact velocities of a binary impact, is frequently used to characterize the amount of energy dissipation associated. We measure the COR by tracing a fre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
3
6
0
Order By: Relevance
“…When increasing the impact velocity further, the slope decreases until a constant value is reached asymptotically, which always stays smaller than the dry coefficient of restitution. This typical trend was also observed for example by Kantak et al (2005), Gollwitzer et al (2012), Müller et al (2013) and Müller and Huang (2016). In accordance to previous experimental works (Antonyuk et al, 2009;Gollwitzer et al, 2012;Crüger et al, 2016a;Ma et al, 2016), an increase in layer thickness, leads to a decrease of the normal coefficient of restitution, because the particle penetrates deeper into the higher liquid layer, resulting in a longer time, the dissipative forces have time to act.…”
Section: Normal Collisionssupporting
confidence: 90%
“…When increasing the impact velocity further, the slope decreases until a constant value is reached asymptotically, which always stays smaller than the dry coefficient of restitution. This typical trend was also observed for example by Kantak et al (2005), Gollwitzer et al (2012), Müller et al (2013) and Müller and Huang (2016). In accordance to previous experimental works (Antonyuk et al, 2009;Gollwitzer et al, 2012;Crüger et al, 2016a;Ma et al, 2016), an increase in layer thickness, leads to a decrease of the normal coefficient of restitution, because the particle penetrates deeper into the higher liquid layer, resulting in a longer time, the dissipative forces have time to act.…”
Section: Normal Collisionssupporting
confidence: 90%
“…3 the (normal) coefficient of restitution in dependence of the collision velocity during normal collisions is compared for the cases "wet wall" (lines) and "wet particle" (circles). As was already described by several authors (Antonyuk et al, 2009;Kantak et al, 2005;Gollwitzer et al, 2012;Müller and Huang, 2016) as well as in our previous work (Crüger et al, 2016a), for small collision velocities a dry particle sticks to a wet wall, leading to a normal coefficient of restitution of zero (e n = 0). After reaching a critical "sticking" velocity the particle is able to rebound (including rupture of the liquid bridge forming during rebound), resulting in a steep increase of the normal coefficient of restitution with increasing collision velocity.…”
Section: Normal Collisionsupporting
confidence: 61%
“…Other authors prefer studying collision dynamics not via non-dimensional parameters, which always incorporate several influencing parameters, but instead investigate each effect individually. Thereby, for example Kantak et al (2005), Gollwitzer et al (2012), Müller et al (2013), Huang (2016), andCrüger et al (2016a) found a characteristic trend of the normal coefficient of restitution with (normal) impact velocity. Additionally, the influence of layer thickness and viscosity were studied for example by Antonyuk et al (2009), Sutkar et al (2015), Crüger et al (2016a,b) as well as Gollwitzer et al (2012).…”
mentioning
confidence: 90%
“…Then ewet,n increases sharply with increasing St M and finally evens out. The observed trend is similar to the findings by many previous studies, among which a few models or correlations have been proposed to predict ewet,n with the Stokes number. We have compared all the existing models (to the knowledge of the authors) with our simulation data.…”
Section: Resultssupporting
confidence: 91%